Development of hybrid magnetorheological elastomers by 3D printing. (1st August 2018) - Bastola, A.K.; Paudel, M.; Li, L.
Abstract: Intelligent or smart materials have one or more properties that can be significantly changed in a controlled fashion by external stimuli, such as temperature, pH, electric or magnetic fields, etc. Magnetorheological (MR) materials are a class of smart materials whose properties can be varied by applying an external magnetic field. In this work, the possibility of employing a suitable 3D printing technology for the development of one of the smart MR materials, the magnetorheological elastomer (MRE) has been explored. In order to achieve such 3D printing, a multi-material printing is implemented, where a controlled volume of MR fluid is encapsulated within an elastomer matrix in the layer-by-layer fashion. The choice of printing materials determines the final structure of the 3D printed hybrid MR elastomer. Printing with a vulcanizing MR suspension produces the solid MR structure inside the elastomer matrix while printing with a non-vulcanizing MR suspension (MR fluid) results in the structures that the MR fluid is encapsulated inside the elastomer matrix. The 3D printability of different materials has been studied by measuring their rheological properties and we found that the highly shear thinning and thixotropic properties are important for 3D printability. The quality of the printed filaments strongly depends on the key printing parameters such as extrusion pressure, initial height and feed rate. The experimental results from the forced vibration testing show that the 3D printed MR elastomers could change their elastic and damping properties when exposed to the external magnetic field. Furthermore, the 3D printed MR elastomer also exhibits the anisotropic behavior when the direction of the magnetic field is changed with respect to the orientation of the printed filaments. This study has demonstrated that the 3D printing is viable for fabrication of hybrid MR elastomers with controlled structures of magnetic particles or MR fluids. Graphical abstract: Image 1 Highlights: 3D printing is applied to fabricate hybrid MR elastomers with controlled structures of magnetic particles or MR fluids. Rheological measurement is performed to study the 3D printability of different materials. Quality of the printed filaments strongly depends on extrusion pressure, initial height and feed rate. 3D printed MR elastomer changes elastic and damping properties and exhibits anisotropic behavior under a magnetic field.